Mineralogical and morphometric aspects of the rock analysis as the basis for choosing a scheme for ore preparation - Duryagina, Asiya; Heide, Gerhard; Talovina, Irina; Bravo, Arturo (E3S web of conferences, 2020)
The complexity of deep processing of fine-grained and refractory mineral raw materials is determined by the difficulty of disclosing aggregates of ore components during disintegration and extracting them into commercial products of standard quality. The main task of the disintegration of such ores is to destroy the object along the phase boundaries without overgrinding while minimizing energy costs. To implement selective disintegration, a precise study of the properties of the mineral components of the ore is necessary. However, there are no systematic data on the effect and relationship of the mineralogical-technological, structural-textural and physical-technical properties of minerals, rocks and ores with the processes of selective disintegration. The article presents the results of computer microtomographic and optical-microscopic studies of the structural and textural characteristics of typical sulfide copper-nickel ores using a SkyScan-1173 microtomograph from Bruker (Belgium), as well as a specialized, accredited as a measuring tool, Thixomet Pro software (Russia). The studies made it possible to identify automatically 19 morphometric parameters of ore grains in three mutually perpendicular sections, the most informative of which were the grain size of individual ore minerals, their perimeter, distance between grains and grain shape (sphericity, edge roughness, and others). The obtained quantitative characteristics of the structural and textural parameters, the analysis of the granulometric composition of the grains of ore minerals make it possible to assess the possibility of using selective grinding at various stages of ore preparation.